Mental disorders and their comorbidity among 6 to 18 years population in Lorestan province, Iran2015-2016 - Nazari, Hedayat; Safavi, Parvin; Hooshyari, Zahra; Parsamehr, Hosien; Abbasi Motlagh, Farzaneh; Tajipoor, Ameneh; Goodarzi, Zohreh; Shokri Moghadam, Saba Shokri Moghadam; Kumasi Jodaki, Shirin; Salehi Kia, Hamzeh; Veyskarami, Maryam; Beyranvand, Samira (Iranian Journal of Child Neurology, 2022)
Abstract Objectives The profile of mental disorders has been changing over time. The aim of this study was to investigate the prevalence of mental disorders in children and adolescents in the Lorestan province of Iran. Materials & Methods This community-based cross-sectional study was done on 1001 children and adolescents aged 6-18 years from Lorestan province randomly selected by multistage cluster sampling method. Children and their parents were interviewed using the Kiddie-Sads-Present and Lifetime Version (K-SADS-PL). Also, the comorbidities of psychiatric disorders were evaluated. Results According to obtained results, 25.1% of participants were diagnosed to have at least one psychiatric disorder. The prevalence of psychiatric disorders was not significantly different between the two sexes (OR=0.876, P=0.378) and three age groups (P>0.05). this prevalence was significantly higher in rural areas than in urban areas (OR=1.997, P=0) and was significantly lower in children of fathers with a high school diploma or higher education compared to children of less-educated fathers (P<0.05). On contrary, it was significantly more prevalent in children of mothers with high school and bachelor’s degrees compared to illiterate mothers. (p<0.05). The most prevalent psychiatric disorders were oppositional defiant disorder (ODD) (5.9%), separation anxiety disorder (5.3%), and depressive disorders (5%). The most prevalent groups of psychiatric disorders included anxiety disorders (11.2%), behavioral disorders (9.4%), and mooddisorders (5%). Behavioral disorders were highly comorbid with anxiety disorders (20.7%). Conclusion Mental disorders affect a high proportion of children and adolescents in Lorestan province.There is a need for psychiatric facilities to provide for the needs of families to child mental health services.